Change in Higher Education: Resistance to Change and Managing Resistance to Change A study from the Point of View of Administrative and Academic Managers at Tobruk University-Libya - Taher Mohamed (African Journal of Advanced Pure and Applied Sciences, 2024)
The study looked at underlying causes for employees’ resistance to change and managing resistance to change. the current study also focuses on the identify a statistically significant difference between the managerial level and academic level in relation to the causes of employees’ resistance to change and managing resistance to change. Questionnaires were used to collect data, a stratified purposive sample consisting of 140 managers was selected from the total of 154 managers working at Tobruk University in Libya. Statistical Package for the Social Sciences (SPSS) Version 21 was used to analyze the data. Results showed that lack of change planning is the main factor behind employees’ resistance to change. Also, creating readiness for change is a crucial method for overcoming employees’ resistance to change. However, there is no statistically significant correlation between demographic variables and administrative methods that can be utilized to overcome employees’ resistance to change. Regarding the causes underlying employees’ resistance to change and the administrative methods employed to cope with such resistance, there is no statistically significant difference between the managerial level and the academic level.